What bimodal and unimodal bilinguals can tell us about bilingual language processing. Issue 2 (1st July 2015) - POARCH, GREGORY J.
Abstract : In their review, Emmorey, Giezen and Gollan (Emmorey, Giezen & Gollan) contrast bimodal bilinguals (individuals who are fluent in a signed and a spoken language) and unimodal bilinguals (individuals fluent in two spoken languages) to highlight the implications of bimodal bilingualism for language processing, the cognitive effects of bilingualism, and the neural organization of languages. For this purpose, the authors focus on the evidence for language mixing in bimodal bilinguals (so-called 'code-blends') by hearing children of deaf parents and explore how language co-activation and control differentially impacts the processing of languages compared to unimodal bilinguals. The sustained controlling of two languages from differing modalities in bimodal bilinguals, according to the authors, may lead to modality-specific cognitive advantages in contrast to unimodal bilinguals.